THE TEENAGER AND SPORT AT SCHOOL (Fiep Bulletin - online, 2014)
The aims which justify sports practice, at school, by teenagers, are various, considering that, the present study had as purpose to understand what are the actual objectives that lead teenagers to practice sports activities within the school universe. The methodology was designed according to the qualitative investigations paradigm, having as a reference the case study. The analysis and interpretation of information were made from Theme Units which emerged, mainly, from semi-structured interviews, performed with the teenagers, from records and notes resulting on the observations comprised in the field diaries and from theoretical reference concerning the aspects that constitute the research problem. The issues arisen from the construction of these Theme Units allowed for understanding what are the objectives that lead teenagers to practice sports in the school investigated. First of all, we observed three aims that lead these teenagers to sports practice. We found as first, health concern, the second is the search for free time occupation. And, at last, we point out the presence of a strong worry about aesthetic values, which can be summarized in aversion to fatness, the nightmare of presenting a body with cellulite and their body shape preservation.
Keywords: Teenagers; sports; school; objectives